Gettysburg : a testing of courage - Trudeau, Noah Andre, 1949- (New York : HarperCollins, 2002)
This text presents an account of the July 1, 1863, Civil War battle, covering heightening campaign tensions, commander decisions, and the struggles faced by thousands of soldiers. Balancing his own narrative style with revealing firsthand accounts, including excerpts from the diaries and letters of the men on both sides of the battlefield, the author recounts the heightening tension of the campaign, the life-or-death decisions made by its commanders, and the struggle endured by thousands of its bravest soldiers. Not forgotten are the stories of the noncombatants, the thousands of civilians whose placid lives were swept into the ferocious cauldron.
Confluence -- Roads to Gettysburg -- Battle -- Endings and beginnings.
Includes bibliographical references (p. [643]-678) and index.
Keywords: Gettysburg, Battle of, Gettysburg, Pa., 1863.